Margaret Myers and Carol Wise (eds.), The Political Economy of China-Latin America Relations in the New Millennium. Brave New World - De León Huerta, Roberto (Revista Mexicana de Política Exterior, 2022)
Reseña de Margaret Myers y Carol Wise (eds.), The Political Economy of China-Latin America Relations in the New Millennium: Brave New World, Nueva York, Routledge, 2016, 290 pp.